2020
DOI: 10.1016/j.semcdb.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Upstream regulation of the Hippo-Yap pathway in cardiomyocyte regeneration

Abstract: The response of the adult mammalian heart to injury such as myocardial infarction has long been described as primarily fibrotic scarring and adverse remodeling with little to no regeneration of cardiomyocytes. Emerging studies have challenged this paradigm by demonstrating that, indeed, adult mammalian cardiomyocytes are capable of completing cytokinesis albeit at levels vastly insufficient to compensate for the loss of functional cardiomyocytes following ischemic injury. Thus, there is great interest in ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 108 publications
0
28
0
Order By: Relevance
“…Upstream signaling pathways regulating YAP/TAZ activity have been shown to mediate cellular interactions with a broad range of microenvironmental factors including (i) soluble bioactive ligands ( Yu et al, 2012 ; Cai and Xu, 2013 ; Chen and Harris, 2016 ; Yang et al, 2019 ), (ii) biomechanical cues ( Dupont et al, 2011 ; Kim et al, 2011 ; Nardone et al, 2017 ; Pardo-Pastor et al, 2018 ), (iii) energy, osmotic and hypoxic stress ( DeRan et al, 2014 ; Ma et al, 2015 ; Mo et al, 2015 ), and (iv) inflammation and tissue injury ( Gregorieff et al, 2015 ; Kim H. B. et al, 2017 ; Choi et al, 2018 ; Flinn et al, 2019 ), via a diverse array of surface receptors, cytoskeletal elements and cytosolic signaling proteins, as illustrated in Figure 2 . Hence, by manipulating YAP/TAZ signaling, we can control how stem/progenitor cells change their phenotype in response to external stimulation and microenvironmental cues.…”
Section: Introductionmentioning
confidence: 99%
“…Upstream signaling pathways regulating YAP/TAZ activity have been shown to mediate cellular interactions with a broad range of microenvironmental factors including (i) soluble bioactive ligands ( Yu et al, 2012 ; Cai and Xu, 2013 ; Chen and Harris, 2016 ; Yang et al, 2019 ), (ii) biomechanical cues ( Dupont et al, 2011 ; Kim et al, 2011 ; Nardone et al, 2017 ; Pardo-Pastor et al, 2018 ), (iii) energy, osmotic and hypoxic stress ( DeRan et al, 2014 ; Ma et al, 2015 ; Mo et al, 2015 ), and (iv) inflammation and tissue injury ( Gregorieff et al, 2015 ; Kim H. B. et al, 2017 ; Choi et al, 2018 ; Flinn et al, 2019 ), via a diverse array of surface receptors, cytoskeletal elements and cytosolic signaling proteins, as illustrated in Figure 2 . Hence, by manipulating YAP/TAZ signaling, we can control how stem/progenitor cells change their phenotype in response to external stimulation and microenvironmental cues.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments in neonatal rat cardiomyocytes have shown that miR-199a directly targets the YAP inhibitory kinase TAOK1 and the E3 ubiquitin ligase β-TrCP, thereby impeding YAP degradation and promoting the translocation of YAP into the nucleus (Torrini et al, 2019). Furthermore, observations in mice suggest that increases in YAP abundance and nuclear localization are sufficient to induce the proliferation of cardiac cells and to improve cardiac performance after MI (Flinn, Link, and O'Meara 2020). Here, we found that the ratio of Serine-127-phosphorated YAP (p-YAP) to total YAP abundance was significantly lower (Figures 2A, B), while nuclear YAP levels were significantly greater, in AAV6-miR-199a-than in AAV6-FIGURE 3 | AAV6miR-199a-tranduced hiPSC-CMs were more potent than AAV6-Control-transduced hiPSC-CMs for myocardial recovery in a mouse MI model.…”
Section: Mir-199a Overexpression Activated the Yes-associated Protein Signaling Pathway In Hipsc-cmsmentioning
confidence: 99%
“…In addition to TEADs, studies have identified many other YAP/TAZ co-factors such as SMAD family members (SMADs) [ 41 , 42 , 43 , 44 , 45 , 46 ], β-Catenin [ 20 ], pituitary homeobox 2 (PITX2) [ 47 ], forkhead box protein O1 (FOXO1) [ 48 ], T-box transcription factor TBX5 [ 49 , 50 ], Runt-related transcription factor 1/2 (RUNX1/2) [ 51 , 52 , 53 , 54 ] and YAP/TAZ competing factors such as vestigial-like family member 4 (VGLL4) [ 55 , 56 , 57 ] ( Figure 1 ). Hippo signaling activity can be regulated by variable upstream factors like kidney and brain expressed protein (KIBRA) [ 58 ], neurofibromin 2 (NF2) [ 58 ], FERM domain-containing protein 6 (FRMD6) [ 59 ], mitogen-activated protein kinase kinase kinase kinases (MAP4Ks) [ 60 ], striatin-interacting phosphatases and kinases (STRIPAK) [ 61 ], serine/threonine-protein kinase 25 (STK25) [ 62 ], P2Y 2 nucleotide receptor (P2Y 2 R) [ 63 ], thousand-and-one amino acid kinases 1/3 (TAOK1/3) [ 64 , 65 , 66 ] and protocadherin Fat4 (FAT4) [ 67 ]. GPCRs (G-protein-coupled receptors) regulate Hippo signaling via GPCRs-G-protein-cytoskeleton axis [ 68 , 69 ] ( Figure 1 ).…”
Section: Overview Of the Hippo Pathwaymentioning
confidence: 99%